Lessons learnt from previous local sustainability efforts to inform local action for the Sustainable Development Goals. Issue 129 (March 2022) - Ningrum, Dianty; Malekpour, Shirin; Raven, Rob; Moallemi, Enayat A.
Abstract: In a world faced with constant and varied sustainability challenges, local communities stand at the forefront of global sustainability efforts. What happens at the local level may affect the larger social and environmental systems. Meanwhile, global environmental impacts are also experienced locally. The current global sustainability agenda, Agenda 2030, calls for local action to realise the Sustainable Development Goals (SDGs). However, we have limited understanding of what enables and constrains local action, particularly in the context of the challenges related to trade-offs between goals, the complexity and uncertainty embedded in the social and environmental systems, and the necessity to align efforts with multiple levels of governance. In this paper, we aim to synthesise lessons learnt from the application of a previous major local sustainability agenda, Local Agenda 21 (LA21), to inform local action for the SDGs. Using a systematic review of 87 empirical cases of LA21 all around the world, we find that availability of reliable resources, supportive planning and policymaking practice, competent local actors, and trust between local actors appear most frequently as enablers of local sustainability processes in the context of LA21. In the end, we discuss the implications of these findings for SDGs implementation at the local level. Highlights: We identify enablers and constraints to the key elements of Local Agenda 21. There were four most frequent enablers to Local Agenda 21 processes. These enablers are resources availability, supportive planning and policymaking practice, competent local actors, and trust. Findings and discussions from this paper can be used to anticipate key concerns in the local implementation of the SDGst.